PENGARUH VEGETASI LANSKAP TERHADAP KENYAMANAN PENGUNJUNG PADA KOMPLEK CEMARA ASRI PADA WAKTU TIDAK HUJAN - Endi Martha Mulia; Muhammad Amin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
A good design of landscaping vegetation may affect visitors’ convenience level. High convenience level could affect the number of visiting, which stimulated the economy happening at Cemara Asri Residence. The convenience mentioned in this report was the one which was from the temperature. To reveal the convenience level, data analysis was done through temperature measurement at Cemara Asri Residence. The measurement was held at four sites with different kinds of vegetation, consist of trees, shrubs, herbs, and bushes. This was also held during seven days and at three different times, which were in morning, afternoon, and evening. Conclusion from the result states that the convenient conditions for the visitors are in the morning and evening. Meanwhile, unconvenient condition is in the afternoon.